Household air pollution during COVID‐19 pandemic: A concern in India. Issue 4 (20th July 2021) - Rani, Ritu; Arokiasamy, Perianayagam; Sikarwar, Ankit
Abstract : Household air pollution is a serious public health concern in India with more than half of the Indian households relying on solid fuel use. The long periods of lockdown related measures to control COVID‐19 pandemic in India further aggravated the adverse health effects of household air pollution as millions Indians were exposed to high level of health‐damaging air pollutants inside their homes. This commentary discusses the vulnerability of the socioeconomically disadvantaged population forced to stay indoors during the pandemic. Exposure to household air pollution has detrimental effects on health, which might put individuals at higher risk for complications related to COVID‐19. A large proportion of socioeconomically disadvantaged section of the population were exposed to critical levels of household air pollution and more vulnerable to severe health effects of COVID‐19. There is a pressing need to understand the aggravated health consequences of household air pollution in association with COVID‐19.